Effectiveness and safety of the interleukin 6-receptor antagonist tocilizumab after 4 and 24 weeks in patients with active rheumatoid arthritis: the first phase IIIb real-life study (TAMARA). Issue 5 (27th December 2010) - Burmester, Gerd R; Feist, E; Kellner, H; Braun, J; Iking-Konert, C; Rubbert-Roth, A
Abstract : Objectives: To confirm the effectiveness and safety of the interleukin 6-receptor antagonist tocilizumab in patients with rheumatoid arthritis (RA) in a setting close to real-life medical care in Germany. Methods: A multicentre open-label phase IIIb study was undertaken. Patients with active RA with a 28-joint Disease Activity Score (DAS28) >3.2 despite previous disease-modifying antirheumatic drugs (DMARDs) were treated with tocilizumab 8 mg/kg every 4 weeks. The primary end point was the proportion of patients achieving LDAS ≤3.2 at week 24; secondary end points included American College of Rheumatology (ACR), European League Against Rheumatism (EULAR) or Clinical Disease Activity Index (CDAI) responses and decrease in acute phase. Analyses in subgroups such as rheumatoid factor (RF)-positive versus RF-negative patients and patients with an inadequate response to treatment with DMARDs (DMARD-IR) versus those with an inadequate response to tumour necrosis factor (TNF) antagonists (TNF antagonist-IR) were performed. Safety was assessed by adverse event documentation. Results: 286 patients were treated and 83.6% completed the study. 41.6% had previously been treated with TNF antagonists. 57% of the intention-to-treat patients achieved the primary end point of LDAS, 47.6% achieved DAS remission <2.6 and a EULAR 'good response' was achieved by 54.9%; ACR50/70 response rates at week 24 were 50.7% and 33.9%, respectively. The mean±SD decrease in CDAI from baseline to week 24 was 71±29%. C reactive protein levels normalised rapidly within 1 week. Major improvements in fatigue, pain and morning stiffness were observed in the first 4 weeks and further improved until week 24. DAS28, EULAR and ACR responses at week 24 did not differ between RF-positive and RF-negative patients. TNF antagonist-naive patients responded better than patients who had previously failed on TNF antagonists. The safety profile of tocilizumab was comparable to that previously observed in the phase III trial programme. Serious infections were observed in 3.1% of patients. Conclusions: Tocilizumab is highly effective in a setting close to real-life medical care with a rapid and sustained improvement in signs and symptoms of RA. A manageable safety profile was seen over the 24-week study period.